Myoglobin Interactions with Polystyrene Surfaces of Different Hydrophobicity. Issue 2 (20th October 2013) - Muntean, Stela‐Andrea; Michels, Matthias A. J.; Lyulin, Alexey V.
<x xml:space="preserve">Abstract</x> The atomistic molecular‐dynamics simulations of the initial stage of myoglobin adsorption on amorphous polystyrene surfaces with varying hydrophobicity are presented. The polystyrene surfaces as non‐oxidized (hydrophobic) and oxidized (hydrophilic) films, both in united‐atoms and dummy‐hydrogen atoms representations are modeled. The protein is placed initially at different distances and orientations from the polymer. We monitor the interactions between the protein and the polystyrene surface for the same polystyrene surface in contact with the protein in different initial orientations and for one initial orientation of the protein in contact with different polystyrene surfaces. By comparing the stability and the number of myoglobin‐polystyrene atomic contacts and the interaction energies, it is found that the initial contact of the protein with the hydrophobic polystyrene surfaces is stronger than with the hydrophilic ones. The orientations of the myoglobin in which the more rigid protein parts face the polymer exhibit stronger initial contact with the polymeric surface.<inline-graphic xlink:href="ark:/27927/pgg4svnfsp5" content-type="mats201300133-gra-0001" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />